THE RELATIONSHIP BETWEEN LEARNERS’ AUTONOMY AND ACHIEVEMENT IN LEARNING ENGLISH (A Descriptive Research at the Students of Islamic University of Indragiri UNISI, Tembilahan - Riau in the Academic Year of 2019/2020) - Agus Mustajib Mustajib (INOVISH JOURNAL, 2020)
The purpose of this research was to find out whether is any relationship between learners’ autonomy and their achievement in learning English. The method used in this research was the descriptive quantitative research. The population of this research was the students of students of Islamic University Indragiri in the academic year of 2019/2020).  The sample of this reaserch was 179 students at second semester that consist six classes. Therefore, this research used total sampling. In collecting the data, this research used written test as the research instrument to find out whether is any relationship between learners’ autonomy and their achievement in learning English at Islamic University Indragiri UNISI. The result of the research showed that every variable which was variable X (learners’ autonomy) and variable Y (learners’ achievement). Both of  variable has a different score, variable X has total score 14326,  and an average score 80.03 with the interpretation high category, meanwhile a variable Y has total score 13954.43 , and  an average score  77.95 with  the interpretation high category. Based on those findings, researchers analyzed the relationship between learners' autonomy and their achievement using the Pearson r formula. It was found out that there was a positive correlation between learners’ autonomy and their achievement in learning English. It was proved by the value of rxy of the correlation was greater than rtable. The value of rxy was 0.134 when the researchers consulted it to the rtable with df (degree of freedom) is N – nr = 179  -  2 = 177. We found that rtable had a value 0.1233 of 1% and 0.1467 of 5%. it could be seen obviously that the value of rxy is greater than the rtable. The hypothesis statement which reads the learners’ autonomy gave a useful contribution in achievement of learning English. Autonomy and achievement has correlation. The learners’ autonomy was enough to achievement in learning English become better.